UMP, Yayasan UMP seal partnership with MEC - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 6 July 2022 – Universiti Malaysia Pahang (UMP) and Yayasan UMP entered into an agreement with the German Malaysian Engineering Community (MEC) to improve graduate employability through the implementation of the German Industry Employability Programme (GIEP) which will benefit students for career placement in Germany.